The shamaness in Asia: gender, religions and the state - Torri, Davide; Roche, Sophie (Routledge, 2021)
The shamaness at the threshold : gender, religions and the state in Asia / Sophie Roche and Davide Torri -- The shamaness' new clothes. On the qualities of resisting bodies / Davide Torri -- Shamanesses high and low : gender-based relationships to spiritual entities in Siberia / Roberte Hamayon -- Retrospectives : what I got wrong in my first book / Laurel Kendall -- Shamanism and gender (in)equality in South and South-east Asia : the chepang of Nepal and the semang-negrito of Peninsular Malaysia / Diana Riboli -- Shamans, Islam and the state medical policy in post-Soviet Kazakhstan and Kyrgyzstan / Danuta Penkala-Gawęcka -- From clanic shamaness to Burkhanist messenger transformations of religious roles of Altaian women (19th-21st centuries) / Clément Jacquemoud -- "Let me take your pain away" : female shamanism in Central Asian soundscape / Razia Sultanova -- Female shamanhood in the southern Siberia at the turn of millennium : a revival of an ancient archetype, modernization or declining of "traditional" shamanism? / Galina B. Sychenko -- Women's sociability : the qalandar khona of Khujand (Tajikistan) in the context of political events / Sophie Roche -- Shamanism and gender construction among the Kavalan of Taiwan : men and women's illness caused by different spirits / Pi-chen Liu -- Mirroring values in possession ritual : a biographic-narrative study of female participants in the zār ritual in the hormozgān province of Iran / Maryam Abbasi -- Shamanism in Mongolia : women, mother-earth and the world / Laetitia Merli.
Keywords: Aufsatzsammlung; Schamanin; Asien